PENGARUH PERMAINAN DAN MOTIVASI ANAK TERHADAP PENGUASAAN KONSEP MATEMATIKA ANAK USIA DINI - Athur Nina Pratiwi (Jurnal Pendidikan, 2012)
The objectives of this research is to identify the significance game and motivation on the mastery of mathematical concepts. The monopoly and snake-ladder games are chosen for the game variable, while motivation variable proposes high and low motivational strenghts. The method of this research is experiment, and the research design is treatment by level 2x2. The hypotheses of the research are tested by two-way variant analysis (ANAVA). The results of the research show that: (1) the mastery on mathematical concepts of students with monopoly game is higher than those with snake-ladder game, (2) there is significant influence of game and motivation towards the mastery of mathematical concepts, (3) in the group of students who belong to the high motivational strength, monopoly game helps them perceive the higher mastery of matematical concepts than  snake-ladder game,    (4) in the group of students who belong to the low motivational strength, snake-ladder game helps them perceive the higher mastery of matemayical concepts than  monopoly game.